Royal Mercy in Later Medieval Scotland - Neville, Cynthia J. (Florilegium, 2012)
This article examines the link between grants of the king's peace in later medieval Scotland and the early elaboration of the royal prerogative of mercy. It argues that the kings of Scotland deeply admired the power to forgive that their English counterparts enjoyed and consciously sought to emulate it. Despite the long survival in Scotland of legal customs that compelled serious offenders to compensate victims of violence, a key period in the development of the Scottish notion of royal mercy occurred in the thirteenth century. Alexander III (1249-1286), in particular, found new ways to extend the royal peace over increasingly wide stretches of the Scottish realm and in doing so also acquired the means to exercise clemency to persons who breached that peace.